Zonulin, regulation of tight junctions, and autoimmune diseases - Fasano, Alessio (Annals of the New York Academy of Sciences, 2012)
Recent studies indicate that besides digestion and absorption of nutrients and water and electrolytes homeostasis, another key function of the intestine is to regulate the trafficking of environmental antigens across the host mucosal barrier. Intestinal tight junctions (TJs) create gradients for the optimal absorption and transport of nutrients and control the balance between tolerance and immunity to nonself antigens. To meet diverse physiological challenges, intestinal epithelial TJs must be modified rapidly and in a coordinated fashion by regulatory systems that orchestrate the state of assembly of the TJ multiprotein network. While considerable knowledge exists about TJ ultrastructure, relatively little is known about their physiological and pathophysiological regulation. Our discovery of zonulin, the only known physiologic modulator of intercellular TJs described so far, has increased our understanding of the intricate mechanisms that regulate the intestinal epithelial paracellular pathway and has led us to appreciate that its upregulation in genetically susceptible individuals leads to autoimmune diseases.